2009
DOI: 10.1094/mpmi-22-2-0222
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Lipoxygenase ZmLOX3 Increases Susceptibility of Maize to Aspergillus spp.

Abstract: Plant and fungal lipoxygenases catalyze the oxidation of polyunsaturated fatty acids, creating fatty acid hydroperoxides (oxylipins). Fungal oxylipins are required for normal fungal development and secondary metabolism, and plant host-derived oxylipins interfere with these processes in fungi, presumably by signal mimicry. The maize lipoxygenase gene ZmLOX3 has been implicated previously in seed-Aspergillus interactions, so we tested the interactions of a mutant maize line (lox3–4, in which ZmLOX3 is disrupted)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 32 publications
2
89
0
1
Order By: Relevance
“…9-LOX-derived oxylipins are also involved in plant growth and development and in stress response. For example, 9-LOX-derived oxylipins are involved in lateral root development in Arabidopsis and maize (Zea mays) (Vellosillo et al, 2007;Gao et al, 2008) and in defense against bacterial pathogens in pepper (Capsicum annuum) and Arabidopsis (Vellosillo et al, 2007;Hwang and Hwang, 2010;Ló pez et al, 2011) and against fungal pathogens and nematodes in maize (Gao et al, 2007;Gao et al, 2008;Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…9-LOX-derived oxylipins are also involved in plant growth and development and in stress response. For example, 9-LOX-derived oxylipins are involved in lateral root development in Arabidopsis and maize (Zea mays) (Vellosillo et al, 2007;Gao et al, 2008) and in defense against bacterial pathogens in pepper (Capsicum annuum) and Arabidopsis (Vellosillo et al, 2007;Hwang and Hwang, 2010;Ló pez et al, 2011) and against fungal pathogens and nematodes in maize (Gao et al, 2007;Gao et al, 2008;Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2007) recently suggested that oxylipin metabolism mediated by a specific 9-LOX, ZmLOX3, may be involved in fungal pathogenesis in maize (Zea mays). ZmLOX3 loss-of-function mutants are susceptible to Aspergillus flavus and Aspergillus nidulans infection (Gao et al, 2009).…”
mentioning
confidence: 99%
“…Brassinosteroids (BR), a class of plant hormone with essential roles in plant growth and development, are perceived by LRR-RK BRI1, which is structurally similar to the PRR FLS2 (Belkhadir et al 2006 ). BAK1 is a positive regulator of PAMP-triggered plant immunity and it acts as an adaptor of multiple LRR-RKs that act in defense signaling, including the PRRs FLS2, EFR, PEPR1 and PEPR2 (Chinchilla et al 2007a , b ;Ryan et al 2007 ;Gao et al 2009a ;Postel et al 2010 ;Schulze et al 2010 ). It also acts as an adaptor of the receptor kinases BIR1 and SOBIR1, which seem to act as part of a presumed PRR complex(es) and/or at a downstream step in the signaling cascade (Saijo 2010 ).…”
Section: Signaling Adapters/amplifi Ers In Pamp-prr Signaling Complexmentioning
confidence: 99%
“…It also acts as an adaptor of the receptor kinases BIR1 and SOBIR1, which seem to act as part of a presumed PRR complex(es) and/or at a downstream step in the signaling cascade (Saijo 2010 ). BAK1 forms a complex with the RLK BIR1 to negatively regulate defense responses (Gao et al 2009a ). BIK1 is a receptor-like cytoplasmic kinase (RLCK).…”
Section: Signaling Adapters/amplifi Ers In Pamp-prr Signaling Complexmentioning
confidence: 99%